Electromagnetic anisotropy and bianisotropy a field guide - Mackay, Tom G. (World Scientific Pub. Co., 2010)
The topics of anisotropy and bianisotropy are fundamental to electromagnetics from both theoretical and experimental perspectives. These properties underlie a host of complex and exotic electromagnetic phenomena in naturally occurring materials and in relativistic scenarios, as well as in artificially produced metamaterials. As a unique guide to this rapidly developing field, the book provides a unified presentation of key classic and recent results on the stsudies of constitutive relations, spacetime symmetries, planewave propagation, dyadic Green functions, and homogenization of composite materials. The book offers an up-to-date extension to standard treatments of crystal optics with coverage on both linear and weakly nonlinear regimes.